Les derniers feux de l’Écorcherie : la chevauchée de Robert de Flocques et Poton de Xaintrailles (printemps 1445) - Christophe Furon (Bulletin du Centre d’Études Médiévales d’Auxerre)
In the spring of 1445, what could be considered like the last pillages of the écorcheurs: in the Burgundian territories, the French captain Robert de Flocques plunders the south of the duchy of Luxembourg and then, joined by the captain Poton de Xaintrailles, the county of Rethel and the castellany of Château-Regnault. These pillages take place in the context of the military reform initiated by Charles VII and of the negotiations between the king and the duchess of Burgundy in Reims and Châlons-en-Champagne. Based on partially unpublished documents from the Archives départementales de la Côte-d’Or, this article analyses the economical, geopolitical and diplomatic matters of these pillages which throw light on the application of the military reform and the development of the negotiations. In that case, the pillages are the way of reaffirming royal authority.